1990
DOI: 10.1007/bf01744139
|View full text |Cite
|
Sign up to set email alerts
|

A study of β-thromboglobulin and platelet factor-4 plasma levels in steady state sickle cell patients

Abstract: To evaluate the platelet function in sickle cell syndromes we measured the beta-thromboglobulin (beta-TG) and platelet factor 4 (PF-4) plasma values of 45 patients suffering from homozygous sickle cell anaemia (10) and sickle cell beta-thalassaemia (35) in steady state. The results were compared to those of 32 normal controls. Both the beta-TG and PF-4 levels were found to be significantly higher in patients than in controls but the beta-TG:PF-4 ratio was significantly lower in the patients group. This finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Not only do vasoocclusive crises occur during inflammatory insults such as infections or surgery, but the steady-state patient has elevated leukocyte counts (3,55), activated leukocytes (7,21,25,33,59) and platelets (1,39,56), elevated cytokines (14,23,34), and circulating endothelial cell adhesion molecules (13). Vasoocclusion in sickle cell disease is transient and episodic (18,29), which would promote tissue ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 98%
“…Not only do vasoocclusive crises occur during inflammatory insults such as infections or surgery, but the steady-state patient has elevated leukocyte counts (3,55), activated leukocytes (7,21,25,33,59) and platelets (1,39,56), elevated cytokines (14,23,34), and circulating endothelial cell adhesion molecules (13). Vasoocclusion in sickle cell disease is transient and episodic (18,29), which would promote tissue ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 98%
“…Other investigators also have provided evidence for platelet activation, including elevated plasma β‐thromboglobulin levels ( Mehta, 1980; Adamides et al , 1990 ), decreased platelet ADP/ATP ratios ( Buerling‐Harbury & Schade, 1989), increased urinary thromboxane metabolites ( Kuranstin‐Mills et al , 1994 ), and increased platelet procoagulant activity ( Tomer et al , 1992 ). Browne et al (1996 ) demonstrated increased plasma and decreased platelet thrombospondin‐1 levels in sickle cell anaemia patients, which most probably reflects ongoing platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that platelets are activated in SCD ( Mehta & Mehta, 1980; Buchanan & Holtkamp, 1981; Mehta, 1980; Adamides et al , 1990 ; Buerling‐Harbury & Schade, 1989; Kuranstin‐Mills et al , 1994 ; Tomer et al , 1992 , 1994; Hebbel et al , 1993 ; Browne et al , 1996 ). The precise mechanism for the apparent platelet activation in these patients has not been established, nor have the circumstances of its occurrence.…”
mentioning
confidence: 99%
“…Thrombocytosis and several qualitative platelet abnormalities, including defects in platelet aggregation and evidence for in vivo platelet activation, have been described in patients with SCD (6)(7)(8)(9)(10)(11)(12)(13)(14). While some studies have suggested that platelets contribute to vasoocclusive crisis (15)(16)(17)(18), there is considerable doubt about their role (19) because antiplatelet agents have not significantly altered the frequency or severity of pain crisis (20-22;22-24).…”
Section: Introductionmentioning
confidence: 99%